Studies on the hypsochromic shifted optical properties of gold nanoparticles embedded electrospun poly(methyl methacrylate) (PMMA) nanofibers. (2020) - Philip, Princy; Jose, Tomlal; Philip, K.C.; Manoj, P.; Sajini, T.
Abstract: Electrospinning is always a fascinating fiber formation technique in the material science world. The characteristic properties and functionalities of the electrospun nanofibers keep them attractive always and everywhere. Here PMMA electrospun nanofibers with 60–150 nm are produced and characterised by various characterisation techniques. Gold nanoparticles (AuNPs) incorporated electrospun PMMA nanofibers are produced by dispersion of the prepared PMMA nanofibers in colloidal AuNPs. The homogenous distribution of AuNPs on PMMA fiber surface is proved by TEM, FESEM, XRD, FTIR etc. and the optical characterisations are done by UV and PL analyses. PL spectra of the AuNPs incorporated PMMA nanofibers showed the characteristic absorptions of both PMMA and AuNPs in the visible region which shows the successful incorporation of the gold nanoparticles to PMMA nanofibers. The PL spectrum shows a characteristic blue shift in peak position with increase in excitation wavelength. The AuNPs incorporated PMMA nanofibers show enhanced photoluminescence than pure PMMA nanofibers which points to the host matrix nature of PMMA to noble metal nanoparticles like AuNPs.